New Trend to Measure the Saturation Point and Suction in Granular Soil - Ahmed Al-Gharbawi; Mohammed Fattah; Mahmood Mahmood (Engineering and Technology Journal, 2020)
There are many methods to measure the suction and saturation point of any soil and the most used is Tensiometer. The objective of this research is to investigate a new trend to measure the saturation point and suction by using soil moisture content sensors (SMCS) and compare the procedure with tensiometer for the granular soil. The soil in this study has been prepared at three relative densities (5%, 35% and 75%) used. The results show that the readings of SMCS become stable when the water content is more than 20% with different relative densities. The relative density did not affect the SMCS reading when approximately reaching the saturation point.